Processos de identificação de professores de inglês em tempos de pandemia - Moreira, Luana Dornelles (2022)
This research is part of the studies developed by the Center of Collaborative Studies in School Contexts (N.E.C.C.E., in Portuguese) and is associated to the umbrella project Línguas na Escola: formação colaborativa de professores de português e inglês para o ensino dos multiletramentos no contexto escolar, which aims to carry out a continuing process of reflection, providing that the participants develop a meta-awareness about the manner that they teach and learn to teach language (TICKS; PINTON, 2020). In addition, Línguas na Escola envisages the development of studies that build collaborative processes between university and school. We understand the pertinence of turning our gaze to the school in the pandemic context, since its impact in education has led to a sudden change in the educational practices due to preventive measures against the coronavirus. Considering this scenario, we wonder to which measure the adaptations and the challenges resulting from new practices of remote teaching influence language teachers’ identity processes. Therefore, this research has the objective of analyzing identification processes of teachers from public schools of Santa Maria constituted by their English language teaching practices, built in/through discourse, during COVID-19 pandemics. With qualitative research and, more specifically, ethnography, as methodological basis, we conducted semi-structured interviews with three English teachers from public schools of Santa Maria – RS, in June and July of 2020, which were later transcripted. Following, during the period of august of 2020 to January of 2021, the teachers produced reflexive diaries in order to follow their practices and identity configurations throughout a period of time in remote teaching. As basis for the study of teacher identities, we understand identity as heterogeneous, flexible and unfinished, so that contradictory identities may coexist in a same individual which will always be building them through his/her actions in society and through discourse in social interactions (BAUMAN, 2005; HALL, 2006; MOITA LOPES, 2006; SILVA, 2000). To identify how the teaching practices constitute the participants’ identification processes, materialized in their discourses, we considered the contributions of Critical Discourse Analysis (FAIRCLOUGH, 2003, 2015), more specifically the concepts of Modality and Evaluation, developed based on Halliday (1994). In the analysis of the interviews, we also used as theoretical background discussions developed by Kalantzis, Cope and Pinheiro’s (2020) about the four approaches – Didactic, Authentic, Functional and Critical – which permeate school teaching practices throughout the last decades. Analysing the reflexive diaries, we identified four guiding semantic categories: changing of focus, pedagogical practice, difficulties during the pandemics and self-image. Besides, during the process of analysing the diaries, we equally used as embasement the concept of metaphors (LAKOFF; JOHNSON, 1980; TELLES, 1999) to identify possible images built in the teachers’ discourse. The results show a participants’ common interest of seeking to attend the more immediate needs of students, abandoning the formal curriculum. Yet, the preoccupation in developing autonomous practices which, as a result, would guarantee the students’ feedback of activities and, eventually, a process of pedagogical reconfiguration of the participants that comprehended the development of collaborative, interdisciplinary, digital activities.